Mortality in relation to hepatitis B virus (HBV) infection status among HIV‐HBV co‐infected patients in sub‐Saharan Africa after immediate initiation of antiretroviral therapy. Issue 4 (23rd January 2021) - Mohareb, Amir M.; Kouamé, Gérard Menan; Gabassi, Audrey; Gabillard, Delphine; Moh, Raoul; Badje, Anani; Emième, Arlette; Maylin, Sarah; Ménan, Hervé; Hyle, Emily P.; Delaugerre, Constance; Danel, Christine; et al.
Abstract: It is unknown how past and active hepatitis B virus (HBV) infection affect immunorecovery and mortality in people with HIV who initiate tenofovir‐based antiretroviral therapy (ART). Using data collected between 2008 and 2015, we studied people with HIV in sub‐Saharan Africa initiating immediate ART in the Temprano randomized control trial. We classified participants into HBV groups at ART initiation: hepatitis B surface antigen (HBsAg)‐positive with HBV DNA ≥ 2, 000 IU/ml; HBsAg‐positive with HBV DNA < 2, 000 IU/ml; isolated HBcAb‐positive; resolved infection (HBsAb‐positive/HBcAb‐positive); and HBV non‐immune/vaccinated (HBcAb‐negative). We compared square‐root CD4‐cell count increases using mixed‐effect, non‐linear regression adjusted for age, sex, baseline CD4 cell count, and HIV RNA. We compared all‐cause mortality using Bayesian parametric survival regression. Among 879 participants, 24 (2.7%) had HBsAg with high HBV DNA, 76 (8.6%) HBsAg with low HBV DNA, 325 (37.0%) isolated anti‐HBcAb, 226 (25.7%) resolved HBV infection and 228 (25.9%) HBV non‐immune/vaccinated. We found no significant difference in CD4 cell increases between HBV‐infection groups after adjustment ( p  = 0.16). Participants with HBsAg and high HBV DNA had the highest incidence of all‐cause mortality (1.9/100 person‐years, 95% Credibile Interval [CrI] = 1.0–3.4). By comparison, incidence rates of mortality were reduced by 57% (95%CrI = −79%, −13%), 60% (95%CrI = −82%, −12%) and 66% (95%CrI = −84%, −23%) in those who had isolated anti‐HBcAb‐positive, resolved HBV infection and HBV non‐immune/vaccinated, respectively. In conclusion, individuals with HIV and past HBV infection or isolated anti‐HBcAb‐positive serology, much like HBV non‐immune/vaccinated, experience lower mortality than those with HBsAg and high HBV DNA. Additional HBV‐related management would not be necessary for these individuals.